AGREEMENT BETWEEN THE TEST IN SITTING DURAL DISTENSION (SLUMP TEST) AND DIAGNOSTIC TEST LASÉGUE PHYSIOTHERAPEUTIC OF LUMBOSCIATALGIA (Fiep Bulletin - online, 2013)
Lumbosciatalgia is defined as a disease affecting the lower portion of the spine, characterized by symptoms that suggest a greater irritation of lumbar nerve root. Its incidence is between L4-L5 and L5-S1. Objective: To assess the agreement between the dural distension test in the sitting position (Slump test) and test Lasègue in physical therapy diagnosis of low back pain. Methodology: Volunteers of female and male subjects (n = 23), aged between 30 and 55 years, diagnosed with lomboaciatalgia constituted the sample group (GL = Group lumbosciatalgia) and submitted to two separate assessments, such as interval of 7 days between the same. The 1st evaluation was composed by pain assessment using a visual analog scale for pain (VAS) and the Slump test. Already the 2nd Grading was composed by pain assessment by visual analog scale for pain (VAS) and the Test of Lasègue. The level of significance was set at p > 0,05 Results: The assessment of pain by Visual Analogue Pain Scale (VAS), higher values ??were obtained for the painful symptoms in the 2nd Assessment (3.92 ± 1.10) when compared with the 1st Assessment (3.52 ± 1.05). Upon agreement test, we found the same Kappa values ??for both the categories (K: 0324). There was no statistically significant difference (p> 0.05) in both categories with p = 0121, showing discordance between the tests used for neurological sciatic nerve. Conclusion: It is concluded that the test seated dural distension (Slump test) and test Lasègue showed no agreement on the diagnosis of low back pain physiotherapy.
Keywords: Physiotherapy; Sciatica; Low back pain